2020
DOI: 10.1161/circinterventions.120.008962
|View full text |Cite
|
Sign up to set email alerts
|

Management of Percutaneous Coronary Intervention Complications

Abstract: Complications of percutaneous coronary intervention (PCI) may have significant impact on patient survival and healthcare costs. PCI procedural complexity and patient risk are increasing, and operators must be prepared to recognize and treat complications, such as perforations, dissections, hemodynamic collapse, no-reflow, and entrapped equipment. Unfortunately, few resources exist to train operators in PCI complication management. Uncertainty regarding complication management could contribute to the undertreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 45 publications
0
27
0
1
Order By: Relevance
“…The previous study showed that 24-72% of patients who will undergo PCI tend to experience anxiety symptoms [5]. The symptoms of patients' anxiety include excessive fear of the therapeutic procedure, feelings of tension, fear of uncertainty about the disease, feeling excessive pain, and excessive worrying before patients undergo PCI [6].…”
Section: Introductionmentioning
confidence: 99%
“…The previous study showed that 24-72% of patients who will undergo PCI tend to experience anxiety symptoms [5]. The symptoms of patients' anxiety include excessive fear of the therapeutic procedure, feelings of tension, fear of uncertainty about the disease, feeling excessive pain, and excessive worrying before patients undergo PCI [6].…”
Section: Introductionmentioning
confidence: 99%
“…In longer dissections, initial stenting of the distal margin is warranted to prevent downstream propagation. 9 Maintenance of the guidewire in the true lumen is critical. If guidewire position is lost and the true lumen cannot be regained by advancing a spring-coil wire (favored over polymer-jacketed guidewires), antegrade dissection-re-entry may be considered.…”
Section: Discussionmentioning
confidence: 99%
“…If guidewire position is lost and the true lumen cannot be regained by advancing a spring-coil wire (favored over polymer-jacketed guidewires), antegrade dissection-re-entry may be considered. 9 Retrograde wiring may facilitate anterograde stenting. 8 Emergency coronary artery bypass graft surgery is required when these methods fail.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical feasibility of performing both IVUS and invasive FFR on the same patient is low. Both IVUS and invasive FFR are interventional exams with the traits of being high risk and requiring a lot from the operator ( 7 , 8 ). Performing IVUS and invasive FFR at the same time will prolong the operation time and increase the risk of surgery.…”
Section: Introductionmentioning
confidence: 99%